1993
DOI: 10.3109/17453679308993620
|View full text |Cite
|
Sign up to set email alerts
|

Low-vs high-viscosity cement in hip arthroplasty: No radiographic difference in 226 arthrosis cases followed for 5 years

Abstract: In 1984 and 1985, 352 hips were randomly assigned to total hip arthroplasty with either low- or high-viscosity cement at 5 Swedish orthopedic departments. Of the 267 hips finally included in the study, 226 were examined clinically and radiographically after 54-77 months. Radiographically, 21 definite stem loosenings and 1 probable stem loosening were observed (10 percent) and 4 additional stems had been exchanged before the 5-year examination. In the survivorship analysis, 261 stem prostheses were included and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Thus, these findings can only be interpreted as material properties related to bone-cement mixing techniques. These results are not demonstrated in clinical studies [ 32 - 34 ] and are furthermore in contradiction with some clinical data: for example, it is well known that voids are more frequent with high viscosity cement; however, in a study of the survival of 8579 arthroplasties, Havelin et al . [ 35 ] found that poorer results were observed when the femoral component was implanted with low viscosity cement.…”
Section: Voids In the Femoral Cement Mantlementioning
confidence: 74%
“…Thus, these findings can only be interpreted as material properties related to bone-cement mixing techniques. These results are not demonstrated in clinical studies [ 32 - 34 ] and are furthermore in contradiction with some clinical data: for example, it is well known that voids are more frequent with high viscosity cement; however, in a study of the survival of 8579 arthroplasties, Havelin et al . [ 35 ] found that poorer results were observed when the femoral component was implanted with low viscosity cement.…”
Section: Voids In the Femoral Cement Mantlementioning
confidence: 74%
“…In this study, Palacos R + G bone cement (Heraeus Medical GmbH, Wehrheim, Germany) was used because it is one of the most widely used commercial cements and has superior antibiotic elution as compared to other commercial cements [35,36]. The environmental conditions used were similar to the ideal conditions for use of bone cement in surgery [37,38]. Antibiotics were selected based on their widespread availability, frequent use in prosthetic joint infections, low price, and biochemical profiles with different molecular weights and solubilities [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (Carlsson et al 1993) we did not find any difference with respect to radiographic stem loosening between collared, flanged and collarless designs. Whether the present findings will have any clinical implications is questionable, but loss of support may jeopardize the stability of the implant.…”
Section: Discussionmentioning
confidence: 52%
“…In a randomized study of low and high viscosity cement in total hip surgery, there was no difference with respect to radiographic component loosening (Carlsson et al 1993). To evaluate the effect of the collar, hips without radiographic signs of loosening were again scrutinized for changes in the upper femur.…”
mentioning
confidence: 99%